The globalization of inflammatory bowel disease: The incidence and prevalence of inflammatory bowel disease in Brazil - Quaresma A.B.* (2019)
© 2019 Wolters Kluwer Health, Inc.Purpose of reviewEpidemiological studies of inflammatory bowel disease (IBD) in newly industrialized countries are limited, due to a lack of medical surveillance systems and reliable and unified registries and databases. In Brazil, reliable data on the incidence and prevalence of Crohn's disease and ulcerative colitis is scarce. The objective of the present review is to describe in detail the available data on the incidence and prevalence of Crohn's disease and ulcerative colitis in Brazil.Recent findingsThe authors identified the single four population-based studies which refer to incidence and prevalence of IBD in the country (two from São Paulo, one from Espírito Santo and one from the state of Piauí). These studies demonstrate a remarkable growth in the incidence and estimated prevalence of IBD in Brazil, with higher number of cases in more developed regions.SummaryThe increase in incidence over time and the higher current prevalence are indicative of a historical progression in relation to the number of IBD patients in our country, similar to what was observed in countries from Asia and approximating those of the northern hemisphere. Epidemiological studies with more accurate methodology are needed in Brazil.